Early Works on Theological Method 3 : Volume 24 - Lonergan, Bernard J. F. (Book collections on Project MUSE., 2013)
Continuing where Volume 23 left off, Volume 24 of the Collected Works of Bernard Lonergan traces the background to Lonergan's notion of functional specialization as it emerges in his Latin courses and seminars on method.